EVALUATION AND COMPARISON OF OPEN AND CLOSED TIBIA SHAFT FRACTURES IN A QUATERNARY REFERENCE CENTER - ALEX DE LIMA SANTOS; CONRADO TAZIMA NITTA; GUILHERME BONI; GUSTAVO TADEU SANCHEZ; MARCEL JUN SUGAWARA TAMAOKI; FERNANDO BALDY DOS REIS (Acta Ortopédica Brasileira, 2018)
ABSTRACT Introduction Tibia shaft fractures are among the most common in orthopedic practice, but Brazilian literature remains limited on the subject. Objective To evaluate the characteristics of tibia shaft fractures and conduct a comparison between exposed and closed fractures of the tibia. Methods This comparative prospective study examined all tibia shaft fractures admitted to our services over a twelve-month period. The cases were evaluated according to age, trauma mechanism, sex, associated fractures, treatment, hospital stay, and readmission rate during the six months after discharge. Results Fifty-three cases met the inclusion criteria. The average age was 36 years (SD 14.3) and 83% were males (p<0.001). Traffic accidents were responsible for 73.6% of fractures (p<0.001). Exposed fractures were found in 52.8% of the cases (p=0.56). When initial treatment consisted of stabilization with external fixation, these cases were more likely to be rehospitalized (p=0.009). Cases of open fracture also had longer hospital stays (p<0.001) and a higher readmission rate (p=0.028). Conclusion Open fractures are associated with more severe trauma, expressed in longer hospital stays and high rates of readmission. Cases of fracture which were initially treated with external fixation had a higher readmission rate. Level of Evidence II; Prospective comparative study.